Heartstopper. Volume 2 - Oseman, Alice (Heartstopper, 2020)
Best friends Nick and Charlie share a spontaneous kiss one day and their relationship changes. Charlie thinks he has made a horrible mistake and ended their friendship, but Nick is not sure what he thinks or feels. Love may find a way between the two yet.